Pengembangan Aplikasi Pembelajaran Fisika Berbasis Android pada Materi Gerak Lurus Kelas X - Tri Hardila; Siti Anisatur Rafiqah; Thoha Firdaus (U-Teach: Journal Education of Young Physics Teacher, 2021)
This study aims to describe the process of developing an Android-based physics learning application on straight motion material in grade 10. The development model used is DDD-E (Decide, Design, Develop, Evaluate). The subjects of this study were three material expert validators, three media expert validators, and 18 grade 10 students at the Mechanical School Engineering Vocational School for the 2020/2021 academic year. Data collection techniques used observation sheets, assessment sheets of media experts and material experts, and practicality trials of student responses which were used as data to determine the practicality of learning applications developed and analyzed with descriptive percentages. The results showed that the validity value of the media expert was 0.84 with high validity criteria and the validity value obtained from the material expert was 0.74 in the medium validity range. The results of the practicality test of student responses showed a value of 80.03% with appropriate criteria. Based on these data, it is concluded that this android-based physics learning application is valid and practical to be used as an independent learning media for students and as a teacher learning media.